Studying and analysis effect level of the Government expenditure and Gross Domestic product in size of the expenditure on the higher education in Iraq (1995 – 2009) - احمد داود عبد الجبار (Journal of Economics and Administrative Sciences, 2012)
The education, especially higher education, is an essentially factor in the progress of any society, if we consider the higher education, represents the top of the education`s pyramid which take part in developing the human resources and provide the human staff to raise the productive efficiency, and improve the social , economic level In order to face the increasing importance of higher education, great capabilities and expenditures must be available in a continous way, such expenditures has increased during the last decade of 20th centaury, because what the society and the government budget into apart of economic and financing resources from expenditure on the section of higher education from Gross Domestic product and Government expenditure .